2007
DOI: 10.1097/01.hp.0000267862.44497.a4
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Assessment of Aluminum Arc Welding Radiation

Abstract: The purpose of this study is to evaluate the non-ionizing radiation (NIR) exposure, especially optical radiation levels, and potential health hazard from aluminum arc welding processes based on the American Conference of Governmental Industrial Hygienists (ACGIH) method. The irradiance from the optical radiation emissions can be calculated with various biological effective parameters [i.e., S(lambda), B(lambda), R(lambda)] for NIR hazard assessments. The aluminum arc welding processing scatters bright light wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
(12 reference statements)
0
9
0
4
Order By: Relevance
“…Ocena nara偶enia zawodowego spawaczy na czynniki szkodliwe jest prowadzona od lat i ukierunkowana na badania zwi膮zk贸w chemicznych wyst臋puj膮cych w py艂ach/dymach (1, 8,9), pola elektromagnetycznego (10--12), a tak偶e promieniowania optycznego (6,7,13,14). Badania wykaza艂y przekroczenia wi臋kszo艣ci normatyw贸w higienicznych, co 艣wiadczy o szczeg贸lnym zagro偶eniu dla zdrowia spawaczy i w efekcie mo偶liwo艣ci wyst臋powania u nich wielu chor贸b zawodowych.…”
Section: Wst臋punclassified
See 2 more Smart Citations
“…Ocena nara偶enia zawodowego spawaczy na czynniki szkodliwe jest prowadzona od lat i ukierunkowana na badania zwi膮zk贸w chemicznych wyst臋puj膮cych w py艂ach/dymach (1, 8,9), pola elektromagnetycznego (10--12), a tak偶e promieniowania optycznego (6,7,13,14). Badania wykaza艂y przekroczenia wi臋kszo艣ci normatyw贸w higienicznych, co 艣wiadczy o szczeg贸lnym zagro偶eniu dla zdrowia spawaczy i w efekcie mo偶liwo艣ci wyst臋powania u nich wielu chor贸b zawodowych.…”
Section: Wst臋punclassified
“…Doniesienia literaturowe dotycz膮ce nara偶enia zawodowego spawaczy na promieniowanie optyczne dotycz膮 r贸偶nych technik spawania 艂ukowego i materia艂贸w spawanych, kt贸re wykonywano zar贸wno w warunkach laboratoryjnych, jak i na stanowiskach pracy. Publikowane wyniki bada艅 ekspozycji zawodowej na stanowiskach pracy dotycz膮 zwykle wybranych metod spawania 艂ukowego materia艂贸w, kt贸re s膮 na nich najcz臋艣ciej spawane (6,7,13,14) i wszystkie wykaza艂y przekroczenie warto艣ci granicznych ekspozycji na promieniowanie nadfioletowe i "艣wiat艂o niebieskie" ustanowionych przez dyrektyw臋 2006/25/WE (16). Wykazano, 偶e nara偶enie na promieniowanie optyczne zwi膮zane jest z rodzajem spawanego materia艂u (6,13) i metod膮 spawania (6,7).…”
Section: Om贸wienieunclassified
See 1 more Smart Citation
“…Studies indicate that UVR exposure with energy above 10 j/cm 2 causes acute responses, including skin erythema, and long-term (chronic) exposure to UVR resulting from sunlight leads to skin cancer (3,5,8). The study by Peng indicated that the permanent use of eye protection equipment in welding can prevent any harm to the corneal layer (9). Furthermore, many relationships have been found between UVR exposure and skin deformation (9).…”
Section: To 400 Nm Wavelength Is Called Ultraviolet Radiation (Uvr) mentioning
confidence: 99%
“…The study by Peng indicated that the permanent use of eye protection equipment in welding can prevent any harm to the corneal layer (9). Furthermore, many relationships have been found between UVR exposure and skin deformation (9). The study by Vatani et al illustrated that welders in the Sarcheshmeh Copper Complex, Kerman, Iran, were exposed to low levels of UVR (UV = 0.09 j/cm 2 ), and thus, the probability for emergence of disease due to UVR was low (10).…”
Section: To 400 Nm Wavelength Is Called Ultraviolet Radiation (Uvr) mentioning
confidence: 99%